PEMBUATAN DAN UJI MUTU FISIK WEDANG UWUH YANG DIKOMBINASIKAN DENGAN BUAH MAHKOTA DEWA (Phaleria macrocarpa L) - Taufiq Taufiq (Akademi Farmasi Yamasi Makassar, 2022)
Wedang uwuh is a typical Imogiri herbal drink which is very rich in benefits. Mahkota Dewa (Phaleria macrocarpa L.) is one of the herbal plants that has many benefits but the processing is not optimal. This study aims to find out how to make wedang uwuh combined with mahkota dewa in order to maximize the processing of mahkota dewa as well as to test of physical quality tests. The process of making simplicia is carried out by the stages of wet sorting, washing, chopping, drying, dry sorting and then weighing based on the concentration of adding the crown of the god as much as 5% and 10%. The preparation was then prepared to perform a physical quality test by extracting each preparation using 85 ml of boiling water and then allowed to stand for 15 minutes. The extracted preparations were then tested for physical quality with the following parameters: Organoleptic test including aroma, color and taste, pH test and viscosity test. The results of this study indicate that in the basic formula, the 5% concentration formula and the 10% concentration formula can be combined with wedang uwuh and the physical quality test meets the physical quality test requirements.